On $G$-derivations of Lie–Yamaguti superalgebras - Abdaoui, Meher; Boujelben, Jamel (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.5Let $G$ be an automorphism group. We study $G$-derivations associated with the Lie–Yamaguti superalgebras. The concept of $G$-derivation, which is a derivation under both bilinear and trilinear operations is defined for the Lie–Yamaguti superalgebras. We also study some important properties of $G$-derivations, as well as with their relationship with other derivations of the Lie–Yamaguti superalgebras.